Decolonizing Research on Heritage Language Maintenance and Loss: - Kharchenko, Nataliya (Advances in Social Sciences Research Journal, 2016)
Abstract The following paper attempts to position a topic of heritage language maintenance and loss from a perspective of postcolonial qualitative research, addressing the issues of voice, and some advantages and limitations of narrative inquiry and interviews as possible research methods. Qualitative research on heritage languages will share most features with the traditional qualitative research, but at the same time will adopt some peculiar additional nuances due to its anti-oppressive and decolonizing stance. Personal interviews and reflective narratives are appropriate methods in the research on heritage language maintenance and loss; however, they are not deprived of limitations. Keywords: qualitative research, decolonizing research, heritage language maintenance, narrative inquiry, interviews.